Implementasi Pembelajaran Akidah Akhlak Dalam Membentuk Karakter Siswa Ar-Rijjal di MTSN 1 Payakumbuh - Ningsih, Fenta Yulia; Monia, Fenny Ayu; Sofriani , Rina; Elfita, Eli; Ermita, Ermita (Indonesian Research Journal on Education, 2023)
Character is something that is not easy to form because in forming the character itself many temptations and distractions will get in the way later. One of the ways to shape character in schools/madrasahs is by applying aqidah morals learning. In other words, even if someone is smart, even if he lacks morals, the knowledge he will have is useless, because knowledge without morals or character will not be useful, because even the devil is smarter than humans, but his character is bad, so he is expelled by God fromheaven. The method used in this research is the descriptive qualitative method, the population is all students at MTsN 1 Payakumbuh, and the sample is class VIII, Ar-Rijal students. The data collection technique uses interview and observation techniques, in which the data analysis techniques are data reduction, data display, and closing drawings. With the aim of how to apply the learning of the moral principles themselves in shaping the character of students. And the results of his research on learning aqidah morals can shape the character of students.